Order Set Usage is Associated With Lower Hospital Mortality in Patients With Sepsis - Christopher R. Dale, MD, MPH; Shelley Schoepflin Sanders, MD; Shu Ching Chang, PhD; Omar Pandhair, MD; Naomi G. Diggs, MD, MBA; Whitney Woodruff, MPH; David N. Selander, MD, MBA; Nicholas M. Mark, MD; Sarah Nurse, MHA, RN; Mark Sullivan, MD, MPH; Liga Mezaraups, MHA, RN; D. Shane O’Mahony, MD (Critical Care Explorations, 2023)
IMPORTANCE:. The Surviving Sepsis Campaign recommends standard operating procedures for patients with sepsis. Real-world evidence about sepsis order set implementation is limited. OBJECTIVES:. To estimate the effect of sepsis order set usage on hospital mortality. DESIGN:. Retrospective cohort study. SETTING AND PARTICIPANTS:. Fifty-four acute care hospitals in the United States from December 1, 2020 to November 30, 2022 involving 104,662 patients hospitalized for sepsis. MAIN OUTCOMES AND MEASURES:. Hospital mortality. RESULTS:. The sepsis order set was used in 58,091 (55.5%) patients with sepsis. Initial mean sequential organ failure assessment score was 0.3 lower in patients for whom the order set was used than in those for whom it was not used (2.9 sd [2.8] vs 3.2 [3.1], p < 0.01). In bivariate analysis, hospital mortality was 6.3% lower in patients for whom the sepsis order set was used (9.7% vs 16.0%, p < 0.01), median time from emergency department triage to antibiotics was 54 minutes less (125 interquartile range [IQR, 68–221] vs 179 [98–379], p < 0.01), and median total time hypotensive was 2.1 hours less (5.5 IQR [2.0–15.0] vs 7.6 [2.5–21.8], p < 0.01) and septic shock was 3.2% less common (22.0% vs 25.4%, p < 0.01). Order set use was associated with 1.1 fewer median days of hospitalization (4.9 [2.8–9.0] vs 6.0 [3.2–12.1], p < 0.01), and 6.6% more patients discharged to home (61.4% vs 54.8%, p < 0.01). In the multivariable model, sepsis order set use was independently associated with lower hospital mortality (odds ratio 0.70; 95% CI, 0.66–0.73). CONCLUSIONS AND RELEVANCE:. In a cohort of patients hospitalized with sepsis, order set use was independently associated with lower hospital mortality. Order sets can impact large-scale quality improvement efforts.